Mechanical thrombolysis as an adjunct therapy to management of portal vein thrombosis following Radio Frequency Ablation - Othman H.A.; Ariffin A.C.; Azman A.; Zuhdi Z.; Jarmin R.; Sang-Yong C. (Societa Editrice Universo, 2024)
Indexed by WOS/SCOPUS